The Influence of Business Strategy and Good Corporate Governance on Company’s Performance - Ait Novatiani, R.; Haizam Mohd Saudi, Mohd; Wedi Rusmawan Kusumah, R.; Fajar, Achmad; Yuniarti, Rita (International Journal of Engineering and Technology, 2018)
In general purpose of a company is to look for the highest profit. An increase in profits shows the company’s performance is good, to ensure that the company’s performance is good, it must be supported by a business strategy and good corporate governance. The purpose of this study is to analyze business strategies and good corporate governance, both partially and simultaneously affect the company’s performance. Sampling technique used in this study non probability namely census sampling which is 46 census sampling. Based on the results of the study, it can be concluded that business strategies and good corporate governance both partially and simultaneously influence the company’s performance